Regular Languages Definable by Lindström Quantifiers (Preliminary Version) - Ésik, Zoltán; Larsen, Kim G. (BRICS Report Series, 2002)
In our main result, we establish a formal connection between Lindström quantifiers with respect to regular languages and the double semidirect product of finite monoid-generator pairs. We use this correspondence to characterize the expressive power of Lindström quantifiers associated with a class of regular languages. Superseded by BRICS-RS-03-28.